Maternal obesity causes fetal cardiac hypertrophy and alters adult offspring myocardial metabolism in mice. (11th May 2022) - Vaughan, Owen R.; Rosario, Fredrick J.; Chan, Jeannie; Cox, Laura A.; Ferchaud‐Roucher, Veronique; Zemski‐Berry, Karin A.; Reusch, Jane E. B.; Keller, Amy C.; Powell, Theresa L.; Jansson, Thomas
Abstract : Abstract: Obesity in pregnant women causes fetal cardiac dysfunction and increases offspring cardiovascular disease risk, but its effect on myocardial metabolism is unknown. We hypothesized that maternal obesity alters fetal cardiac expression of metabolism‐related genes and shifts offspring myocardial substrate preference from glucose towards lipids. Female mice were fed control or obesogenic diets before and during pregnancy. Fetal hearts were studied in late gestation (embryonic day (E) 18.5; term ≈ E21), and offspring were studied at 3, 6, 9 or 24 months postnatally. Maternal obesity increased heart weight and peroxisome proliferator activated receptor gamma ( Pparg ) expression in female and male fetuses and caused left ventricular diastolic dysfunction in the adult offspring. Cardiac dysfunction worsened progressively with age in female, but not male, offspring of obese dams, in comparison to age‐matched control animals. In 6‐month‐old offspring, exposure to maternal obesity increased cardiac palmitoyl carnitine‐supported mitochondrial respiration in males and reduced myocardial 18 F‐fluorodeoxyglucose uptake in females. Cardiac Pparg expression remained higher in adult offspring of obese dams than control dams and was correlated with contractile and metabolic function. Maternal obesity did not affect cardiac palmitoyl carnitine respiration in females or 18 F‐fluorodeoxyglucose uptake in males and did not alter cardiac 3 H‐oleic acid uptake, pyruvate respiration, lipid content or fatty acid/glucose transporter abundance in offspring of either sex. The results support our hypothesis and show that maternal obesity affects offspring cardiac metabolism in a sex‐dependent manner. Persistent upregulation of Pparg expression in response to overnutrition in utero might underpin programmed cardiac impairments mechanistically and contribute to cardiovascular disease risk in children of women with obesity. Key points: Obesity in pregnant women causes cardiac dysfunction in the fetus and increases lifelong cardiovascular disease risk in the offspring. In this study, we showed that maternal obesity in mice induces hypertrophy of the fetal heart in association with altered expression of genes related to nutrient metabolism. Maternal obesity also alters cardiac metabolism of carbohydrates and lipids in the adult offspring. The results suggest that overnutrition in utero might contribute to increased cardiovascular disease risk in children of women with obesity. Abstract : Abstract figure legend Schematic diagram illustrating experimental design and major findings.